The Stages of Property : Copyrighting Theatre in Spain - Surwillo, Lisa (Book collections on Project MUSE., 2007)
Through an integrative historicist approach to a wide range of literary texts and archival documents, The Stages of Property makes an important statement about the cultural, societal, and political roles of the theatre in Spain during the 1800s.